La contribución de Caramuel a la creación de lenguas artificiales: características universales, lenguas filosóficas y lenguas secretas - Martínez Gavilán, María Dolores (Revista de investigación lingüística, 2016)
This article introduces Juan Caramuel's universal language schemes, framing them within the seventeenth century movement towards the creation of artificial languages characterized by the design of a priori schemes. Because of their variety and complexity, Caramuel's schemes deserve a more prominent place in global studies on the subject.